PROGRAM APPLICATION WORKSHOP ON MOTOR SALES SPAREPARTS ON DAFFA MOTORSPORTS - Bagus Galih Permono; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2005)
In a company or organization, a business development company became a benchmark for the success of these companies. In order for the company performance will be maintained, they should be able to mobilize all of all of its operational resources to work optimally. One is the need for application programs to manage existing data. This is due to make the right decisions requires accurate and easily understood. Here the role of database application programs as a provider of computerized data, should be able to provide information in a short time and easy to read. The author takes the case personally at a workshop owned by the author, namely Daffa Motorsport Motor Repair. These workshops are still using manual system in data processing sales, and therefore these data are available spare parts and sales transactions can not be managed effectively. The writer tries to design a sales system in accordance with the needs of spare parts of the bike shop using Visu al Basic 6.0. database based on Microsoft Access.